2018
DOI: 10.1016/j.cognition.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Does a lack of auditory experience affect sequential learning?

Abstract: To understand the interaction between sensory experiences and cognition, it is critical to investigate the possibility that deprivation in one sensory modality might affect cognition in other modalities. Here we are concerned with the hypothesis that early experience with sound is vital to the development of domain-general sequential processing skills. In line with this hypothesis, a seminal empirical study found that prelingually deaf children had impaired sequence learning in the visual modality. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 44 publications
4
41
1
1
Order By: Relevance
“…Whether or not temporally organized auditory feedback from repetitive actions with objects (e.g., shaking noisy objects), as well as early spoken language experience, influences later sequential encoding and retrieval is unclear. Torkildsen, Arciuli, Haukedal, and Wie () recently found, however, that 7‐ to 12‐year‐old deaf children with cochlear implants showed implicit visual sequence learning comparable to that of hearing children.…”
Section: Discussionmentioning
confidence: 97%
“…Whether or not temporally organized auditory feedback from repetitive actions with objects (e.g., shaking noisy objects), as well as early spoken language experience, influences later sequential encoding and retrieval is unclear. Torkildsen, Arciuli, Haukedal, and Wie () recently found, however, that 7‐ to 12‐year‐old deaf children with cochlear implants showed implicit visual sequence learning comparable to that of hearing children.…”
Section: Discussionmentioning
confidence: 97%
“…Further, the results provide little guidance to what specific aspects of language ability could potentially be predicted by NWR. The finding that hearing level was negatively correlated with repetition performance may indicate that the quality of auditory stimulation prior to HA fitting or cochlear implantation is important for NWR, together with a shorter period of auditory deprivation (Torkildsen, Arciuli, Haukedal, & Wie, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…If access to sound were necessary for healthy cognitive development, then all deaf children should be impacted -including those born into households where a sign language is the primary language (in fact, these children might be expected to be impacted most, as many do not routinely use any sort of hearing technology). Contrary to this prediction, recent studies with Deaf native signers have not found evidence of any difficulties in executive function Hall, M. L., Eigsti, B., & Lillo-Martin, D., 2018;Marshall et al, 2015) In addition, there are now three published failures to replicate original observations of an implicit sequence learning deficit in DHH children Klein, Walker, & Tomblin, 2018;Torkildsen, Arciuli, Haukedal, & Wie, 2018).…”
Section: Part 2: Theoretical and Practical Arguments Against Natural mentioning
confidence: 93%